Metasurfaces for control of light propagation and diffractive optics applications - Martins, Augusto (2021)
This PhD thesis describes the design, modelling, fabrication, and characterization of metasurfaces capable of controlling the propagation of light beams with low insertion losses. Metasurfaces are planar subwavelength structures that allow local control of phase, amplitude and/or polarization of light. These structures have proven to be extremely versatile, finding applications in imaging, holography, polarization optics and sensing, to mention only a few. One key aspect in the design of a metasurface is the material choice of its constituents, as it plays a significant role in defining the physical mechanism underlining its operation. In this sense, we can divide metasurfaces into two groups: plasmonic and dielectric. Plasmonic metasurfaces, which use metallic structures, were the first metasurfaces demonstrated in the literature. Nevertheless, the efficiencies of these metasurfaces are severely impacted by Ohmic losses and are theoretically limited in 25% when operating in transmission mode. For example, it is shown in this thesis that the transmission efficiencies of plasmonic metasurfaces based on aluminium are of the order of ~13%, which is typically too low for holography, for instance. Recently, all-dielectric metasurfaces based on high refractive index materials have been proposed as an alternative to circumvent the low transmission problem of plasmonic metasurfaces. In this thesis, it is shown how the transmission efficiencies of metasurfaces are dramatically improved by dielectric materials. The dielectric of choice in this thesis is crystalline silicon (c-Si), which has a combination of advantageous properties, such as: high refractive index, ease of patterning, and low absorption in the visible (as compared to amorphous silicon). Two metasurface designs are then proposed for holography applications. The first design uses cylindrical nanoposts to impose a phase modulation in the transmitted light. The hologram shows high fidelity and high efficiency, with measured transmission and diffraction efficiencies of ~65% and ~40%, respectively. Although originally designed to achieve full phase control in the range [0-2π] at 532 nm, these holograms have also performed well at 444.9 nm and 635 nm. The high tolerance to both fabrication and wavelength variations demonstrate that holograms based on cSi metasurfaces are quite attractive for diffractive optics applications, and particularly for fullcolour holograms. The second design uses elliptical cross-section nanoposts that are form-birefringent, that is, they provide independent control of phase for two orthogonal polarizations in the visible spectrum. Relying on these properties, a holographic stereogram was encoded in the metasurface. Briefly, a stereoscopic image (stereogram) is composed of a pair of orthogonally polarized images taken from the same scene but recorded in slightly shifted positions to replicate the natural parallax of the human eye. For the stereoscopic effect (depth perception) to occur, each of these two images has to be directed to each of the user\'s eyes separately with the help of cross-polarized glasses. The stereoscopic effect is obtained by combining two holograms on the same metasurface (one for each polarization). The hologram was encoded with four phase levels. Two additional non-stereoscopic holograms using two uncorrelated images were also fabricated to help assessing polarization cross-talk. The reconstruction plane consists of a fine-sanded aluminium surface to preserve the polarization of the scattered light. The stereoscopic view is obtained with a pair of cross-polarized filters (or glasses) placed in front of the observers\' eyes. The theoretical bandwidth is 110 nm with a signal to noise ratio (SNR) >15 dB. The measured transmission and diffraction efficiencies are about 70% and 15%, respectively, at 532 nm. Such high efficiency is due to a combination of low absorption and high index of c-Si at visible: the index is sufficiently high to enable sufficiently small posts to alleviate the material losses. We also investigated the metasurfaces at 444.9 nm and 635 nm to experimentally assess their bandwidth performance. The quality of the stereoscopic effect is surprisingly high at 444.9 nm (but not so much at 635 nm) with transmission and diffraction efficiencies around 70% and 18%, respectively. The proposed structure was able to successfully capture the depth effect on the reconstructed images, with potential applications in diverse areas such as visual arts, entertainment, and security. The latter, in particular, will certainly benefit from the increased degree-of-freedom conveyed by stereoscopic information. Leveraging on the experience obtained with the research on holograms, we focused on the problem of monochromatic aberrations on metalenses. Metalenses are nanostructured surfaces that mimic the functionality of optical elements. Many exciting demonstrations had already been made, for example, focusing into diffraction-limited spots or achromatic operation over a wide wavelength range. The key functionality that was yet missing, however, and that is most important for applications such as smartphones or virtual reality, is the ability to perform the imaging function with a single element over a wide field of view. Thus, relaxing the constraint on diffraction-limited resolution, we demonstrated the ability of single-layer metalenses to perform wide field of view (WFOV) imaging while maintaining high resolution suitable for most applications. We also discussed the WFOV physical properties and, in particular, we showed that such a WFOV metalens mimics a spherical lens in the limit of infinite radius of curvature and infinite refractive index. Finally, we explored the expertise acquired with the design of nanostructures to address an important problem in the renewable energy community: how to improve the performance of solar cells using nanostructures. In particular, we analysed the impact of these structures on the performance of a new class of solar cells: the tandem solar cell employing perovskites and silicon. Such tandem solar cells require careful photon management for optimum performance, which can be achieved with intermediate photonic structures. We first identified that a photonic intermediate structure in a perovskite/c-Si tandem solar cell should act as an optical impedance matching layer at the perovskite-silicon interface. This conclusion did not tally with the perception in the tandem community at the time, which tented to ascribe the role of a tailored reflector to intermediate structures. Relying on the new insights gained, we analysed two simple designs and compared their performances with intermediate reflectors based on Distributed Bragg Reflectors (DBR). Our conclusion was that the intermediate structures acting only as an optical impedance matching layer show similar performance as the DBR reflectors but are much simpler. We completed the analysis by simulating a realistic device configuration and showed that optical impedance matching alone can increase the short circuit current of the silicon solar cell by 18.5% (corresponding to a boost of 2.8 mA/cm2), thus resulting in an expected tandem efficiency in excess of 30%.